Optimalisasi Perencanaan Pembelajaran Seni Budaya: Langkah-Langkah Efektif bagi Guru - Sukreni, Desak Nyoman; Laksana, I Nengah Pandu Dwi; Artana, I Nyoman Yoga; Wiguna, Ida Bagus Alit Arta (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This research aims to identify effective steps in optimising cultural arts learning planning at SMK Negeri 5 Mataram and the challenges faced by teachers in its implementation. Through a qualitative approach with a case study design, data was obtained through observation, structured interviews, and documentation. The results show that the preparation of lesson plans that are relevant to the characteristics of students is an important first step, but still lacks attention to differentiation of learning for students with low interest in cultural arts. The discovery learning method, although effective in increasing student engagement, faces challenges related to the limited availability of facilities and infrastructure. In addition, the constraints of students who feel they have the wrong major are the main obstacles in achieving learning objectives. Therefore, optimising lesson planning requires a more flexible and collaborative approach between teachers, students and school authorities. This research contributes to the development of a more innovative and effective cultural arts lesson planning model, by prioritising differentiation and the utilisation of technology and more varied media.